Prediction of preeclampsia in twin pregnancy - Rodrigues, Carla Ferreira Francisco (2018)
Twin pregnancy is a high-risk condition obstetricians have to deal with frequently in clinical practice and its incidence has risen dramatically over the last decades. Additionally, hypertensive disorders including preeclampsia (PE), are amongst the most common medical complications of pregnancy and a major cause of maternal and perinatal morbidity and mortality. While it is unquestionable that multiple pregnancy has an increased risk of PE, it is still unclear what other risk factors are significant in the development of PE in twins. The exact pathophysiology of PE is uncertain. Traditionally it was thought to be a condition of poor placentation, resulting in generalized vascular endothelial activation and vasospasm, with typical cardiovascular clinical manifestations. Recent published data support the hypothesis that an angiogenic/anti-angiogenic balance plays a causative role in endothelial cell injury. The impact of the maternal cardiac function in the development of PE has become more relevant in the last years. The early detection of pregnancies at high-risk of PE could improve the maternal and neonatal outcome by a more individualized patient surveillance and the timely institution of prophylactic measures. In singleton pregnancies, screening for PE in the first trimester using a combined approach has a high detection rate. In twin pregnancies data related to PE screening is limited and inconsistent. The objective of this thesis is to clarify some of the issues with regard to PE in twin pregnancy. We set out to determine the relative risk for total and preterm-PE in multiple pregnancy when compared with singletons. Additionally, the aim is to assess the effect of maternal characteristics and medical history in the prediction of PE in twin pregnancies. The final goal is to develop a screening model for PE in twins by a combination of maternal factors and biomarkers. The research developed consists of three prospective screening studies for PE, with a population of 2219 twin pregnancies. In the first study, we found that there is a hidden high risk of PE in twin pregnancies. Although, as classically described, the relative risk of total PE is about three times higher in twins, the risk of preterm-PE is nine times higher than in singleton pregnancies. In the second study, we evaluated the effect of maternal and pregnancy characteristics on the risk of PE. Screening for preterm PE using maternal factors has a very high detection rate (99-100%) but at the expense of an extremely high screening positive rate (97-99%). In the third study, we developed a model combining maternal characteristics with biophysical and biochemical markers to screen for PE in twin pregnancies. The performance of the screening model for preterm PE was very good with a detection rate for PE before 32 weeks of 100%, at any cut-off used. Once again the screen positive rate was high: 25%, 65% and 75%, using a cut-off 1:10, 1:50 or 1:75, respectively. We believe that increasing the knowledge about PE in twin gestation may allow an improvement in patient’s surveillance, the implementation of an effective screening method and the development of a preventive strategy.